CRITICAL ANALYSIS OF RADIATION DOSE REDUCTION TECHNIQUES IN RADIOLOGICAL IMAGING AND BALANCING PATIENT SAFETY AND IMAGE QUALITY - 1Mohammed Saad Mohammed Alqahtani, 2Ibrahim Sulaiman Madloul Alshammari, 3Abdullah Mubarak Abdullah Alahmari, 4‎Mohammed Saeed ALHajri, ‎5Zammal Mana Zammal Almansour, 6Fahad Ahmad Alaqil, 7Hassan Hadi Alatwah, 8Hamad Ahmed ALNAJRANI, (Chelonian Research Foundation, 2022)
Radiological imaging plays a crucial role in diagnosing various medical conditions, but it comes with the inherent risk of radiation exposure. This article investigates different applications of electronic radiation treatment and their effect on safety and image quality. In a comprehensive writing audit, distinctive techniques for decreasing control estimations and keeping up image quality are examined. This consideration assesses the ampleness of these procedures based on actual proof and gives proposals for the treatment of radiation treatment within the clinical setting. Usually, critical progress in measuring constriction, but issues stay in guaranteeing excellent safety and outstanding image quality. The talks examine the trade-offs associated with dosage diminishments and emphasize the need for different approaches. In rundown, this article highlights the significance of investigation and collaboration among doctors to create strategies to diminish radiation introduction and advance patient of care. Keywords: Radiation dose reduction, radiological imaging, patient safety, image quality, dose optimization